(untitled) (Indian Journal of Public Health Research & Development, 2020)
Anxiety is one of the psychological responses experienced by clients with diabetic ulcers that can affect glycemic control, serious complications, foot self-care behavior and slow the wound healing process. This research used to find out the factors that influence anxiety in clients with diabetic ulcers. This study was a retrospective analysis using medical records and diagnostic results of diabetic ulcers at Haji General Hospital, Surabaya, Indonesia. The sample was 951 people suffering from diabetic ulcers between January 2014 - December 2018. Samples were diagnosed with anxiety based on nursing diagnoses and fulfilling inclusion and exclusion criteria. The multivariable model of diabetic ulcer client anxiety was generated using stepwise logistic regression. There were independent variables affecting the anxiety of diabetic ulcer clients namely wound type (p < 0.015; OR = 0.91), health insurance (p <0.001; OR = 0.77) and gender (p <0.040; OR = 0.98) with the contribution of the four independent variables at 31% and the prediction accuracy of 86.6%. Gender of patients have a risk of 0.98 times experiencing anxiety, male contribute 0.64 times compared to female, so nursing interventions can be focused on wound care.